1999
DOI: 10.1037/0096-1523.25.4.1050
|View full text |Cite
|
Sign up to set email alerts
|

Dynamic frequency change influences loudness perception: A central, analytic process.

Abstract: Three experiments showed that dynamic frequency change influenced loudness. Listeners heard tones that had concurrent frequency and intensity change and tracked loudness while ignoring pitch. Dynamic frequency change significantly influenced loudness. A control experiment showed that the effect depended on dynamic change and was opposite that predicted by static equal loudness contours. In a 3rd experiment, listeners heard white noise intensity change in one ear and harmonic frequency change in the other and t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
58
0

Year Published

2002
2002
2022
2022

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 42 publications
(63 citation statements)
references
References 39 publications
4
58
0
Order By: Relevance
“…Researchers typically argue that pitch and loudness interact because they occur together in a way that makes it efficient to process them holistically (Garner, 1974;Grau & Kemler-Nelson, 1988) or because the context created by one dimension influences perception in the other (Melara et al, 1993;Neuhoff et al, 1999). We suggest that, in nature, there is a reliable correlation and near-invariant relationship between changes in intensity and frequency.…”
Section: Interacting Pitch and Loudnessmentioning
confidence: 99%
See 2 more Smart Citations
“…Researchers typically argue that pitch and loudness interact because they occur together in a way that makes it efficient to process them holistically (Garner, 1974;Grau & Kemler-Nelson, 1988) or because the context created by one dimension influences perception in the other (Melara et al, 1993;Neuhoff et al, 1999). We suggest that, in nature, there is a reliable correlation and near-invariant relationship between changes in intensity and frequency.…”
Section: Interacting Pitch and Loudnessmentioning
confidence: 99%
“…Neuhoff et al (1999) found that continuous frequency change in one ear could influence continuous loudness change in the contralateral ear. A similar process may be responsible for the influence of continuousintensity change on pitch.…”
Section: Interacting Pitch and Loudnessmentioning
confidence: 99%
See 1 more Smart Citation
“…The perception of loudness involves central processes (Neuhoff et al, 1999) and the neural transmission may be affected by efferent control mechanisms (Stenfelt et al, 2009). For example, it has been shown that the auditory evoked amplitude of the neural activity in the 19 brainstem is modulated by the cognitive load (Sörqvist et al, 2012).…”
Section: Efferent Controlmentioning
confidence: 99%
“…Listeners presented with rising or falling frequency sweeps with a constant intensity will perceive an illusory increase or decrease in loudness, respectively (Neuhoff, McBeath, & Wanzie, 1999). It is important to note that rising frequency change affects illusory loudness judgments greater than falling frequency change; that is, human subjects show a bias toward rising versus falling frequency, possibly because the former is perceived as an increase in loudness and thus a looming sound source (Neuhoff & McBeath, 1996).…”
mentioning
confidence: 99%